An IOT Based Landslide Detection and Early Warning System in Hilly Areas: A Case Study of Bududa District, Eastern Uganda - Lusiba, Badru; Semwogerere, Twaibu; Oguti, Victoria; Ocen, Gilbert Gilibrays (East African Nature and Science Organization, 2022)
Landslides are the gravitational movements of soil, rock down slopes that can cause several damages to the environment. It is one of the most common occurring natural phenomena worldwide in causing great loss of lives and property. The study aimed at developing a Web-Based Landslide Detection and Alert System to monitor and alert people in landslide-prone areas in time. Quantitative experimental designs were employed targeting parameters like soil pore pressure, soil vibration, soil movement, rain intensity and humidity. These are sensor-monitored and their values are analysed for the system development. These values are transmitted to the monitoring section via the internet and people get notified by a text “landslide detection alert” by using GSM. Findings are expected to contribute towards disaster preparedness and eventual loss of lives and property. It is therefore recommended for use in such prone areas by the ministry and other organs of concern